UNH-MODAQ: An implementation of NREL’s Modular Ocean Data Acquisition System for the Open-Source Tidal Energy Converter (OSTEC) Project (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Open water testing of marine energy devices is critical for demonstrating the viability of marine energy converters, both at the Powering the Blue Economy and utility scales. During these open water testing campaigns, various data must be collected to characterize the performance, loads, environmental parameters, and survivability of the device during operation. The National Renewable Energy Lab (NREL) developed and maintains the Modular Ocean Data Acquisition (MODAQ) system to coordinate the collection and synchronization of this data.The Open-Source Tidal Energy Converter (OSTEC) project is a collaborative effort between the University of New Hampshire (UNH) – Atlantic Marine Energy Center (AMEC), Sandia National Labs (SNL), the Pacific Northwest National Labs (PNNL), and NREL to design, build, deploy, and test an open-source tidal turbine. The OSTEC turbine will be deployed at the UNH tidal energy test site in the Piscataqua River, NH. This project aims to measure a variety of metrics including performance, device and structural health, and select environmental parameters while the OSTEC turbine is operating in a real tidal flow. In the interest of collecting synchronizing, and managing this data, UNH and NREL worked together to create the UNH-MODAQ, which is a unique implementation of the MODAQ system. A previous iteration of this system was successfully deployed at the UNH tidal energy test site for previous turbine and resource characterization studies. The OSTEC project provided an opportunity to upgrade the functionality, flexibility, and reliability of the UNH-MODAQ system. with the goal of providing data collection and synchronization to future deployments.The measurement and testing objectives of the OSTEC project require the UNH-MODAQ system to interface with a suite of instrumentation and sensors across multiple subsystems. The system is responsible for real-time acquisition of mechanical loads, power performance, control, health monitoring, and data management during the operation of the OSTEC turbine. The two main subsystems in the UNH-MODAQ, one in the rotating hub of the turbine and one on the stationary deployment platform, communicate with each other via Open Platform Communication Unified Network (OPCUA) through a slip ring. The data will be down sampled and uploaded to a web-accessible dashboard (via NREL’s AWS pipeline) where the near real-time data will be available. The system’s hardware and software capabilities will allow the system to continue to evolve to accommodate the data acquisition needs of future projects. A discussion of the key measurements integrated into UNH-MODAQ and the overall capability of the system is described in this work. This data acquisition system incorporates all components of NREL’s data acquisition infrastructure and is a practical test of the MODAQ system in its entirety. This paper provides an example and blueprint on how to expand the NREL MODAQ system for marine energy deployments where a large number of time-synchronized variables must be measured.The National Renewable Energy Laboratory is operated by Alliance for Sustainable Energy, LLC, for the U.S. Department of Energy (DOE) under Contract No. DE-AC36-08GO28308, with funding provided by U.S. Department of Energy Water Power Technologies Office.